Solving coupled Differential equations

1 Ansicht (letzte 30 Tage)
JaeSung Choi
JaeSung Choi am 11 Okt. 2017
Kommentiert: JaeSung Choi am 15 Okt. 2017
I tried to solve following diff. eq. using 'dsolve' but (maybe) it's impossible.
So please help me how to solve following eq.s using matlab!!!!!
syms s1 s2 s3 g1 g2 g3 p1 p2 p3 t
h = 1; b = 2; e = exp(1); v = 1;
diffqp1 = 'Dp1 = h*b*s1*(g1-p3)-(e/v)*p1'
diffqp2 = 'Dp2 = h*b*s1*(g1-p3)-(e/v)*p2'
diffqp3 = 'Dp3 = h*b*s1*(g1-p3)-(e/v)*p3'
diffqs1 = 'Ds1 = -h*b*s1*(g1-p3)-(e/v)*s1'
diffqs2 = 'Ds2 = -h*b*s1*(g1-p3)-(e/v)*s2'
diffqs3 = 'Ds3 = -h*b*s1*(g1-p3)-(e/v)*s3'
  3 Kommentare
Walter Roberson
Walter Roberson am 11 Okt. 2017
  • Are your g1 g2 g3 functions or constants?
  • What boundary conditions are there?
  • you never use g2 or g3 but use g1 repeatedly
Presuming that g1 is a constant and not a function, then current syntax would look like
syms s1(t) s2(t) s3(t) g1 g2 g3 p1(t) p2(t) p3(t)
h = 1; b = 2; e = exp(1); v = 1;
Dp1 = diff(p1); Dp2 = diff(p2); Dp3 = diff(p3);
Ds1 = diff(s1); Ds2 = diff(s2); Ds3 = diff(s3);
diffqp1 = Dp1 == h*b*s1*(g1-p3)-(e/v)*p1;
diffqp2 = Dp2 == h*b*s1*(g1-p3)-(e/v)*p2;
diffqp3 = Dp3 == h*b*s1*(g1-p3)-(e/v)*p3;
diffqs1 = Ds1 == -h*b*s1*(g1-p3)-(e/v)*s1;
diffqs2 = Ds2 == -h*b*s1*(g1-p3)-(e/v)*s2;
diffqs3 = Ds3 == -h*b*s1*(g1-p3)-(e/v)*s3;
eqns = [diffqp1, diffqp2, diffqp3, diffqs1, diffqs2, diffqs3];
sol = dsolve(eqns);
JaeSung Choi
JaeSung Choi am 15 Okt. 2017
Really thanks for your comment. I'm sorry for that I forgot some constants.

Melden Sie sich an, um zu kommentieren.

Antworten (0)

Community Treasure Hunt

Find the treasures in MATLAB Central and discover how the community can help you!

Start Hunting!